Identifikasi Keragaman dan Dominansi Gulma pada Lahan Pertanaman Kedelai - Vidya Imaniasita; Twenty Liana; Krisyetno Krisyetno; Dayu Satriyo Pamungkas (Agrotechnology Research Journal, 2020)
The diversity and dominance of weeds is the first step in determining the success of weed control. This study aimed to identify the diversity and dominance of weeds in the cultivation of soybean under the shade of oil palm that have not produced (1 year). This research was conducted in October 2018 to January 2019. Sampling used a phrase with a frame size of 1 x 1 m. Weed samples were collected and identified per species according to weed groups, then counted with Summed Dominance Ratio to get weed dominance at each location. There were 10 weed families in soybean cultivation consisting of two types of weed grass, seven types of broadleaf weeds, and two types of weed puzzles. The dominant weed family in soybean cultivation was found in the Poaceae family, with Imperata cylindrica species.